Udayana COVID-19 Scoring System: a simple diagnosing aid for early detection of COVID-19 (Research, Society and Development, 2023)
Coronavirus Disease-19 (COVID-19) is a highly transmittable disease. While the most common symptoms of COVID-19 include fever, cough, and fatigue, severe symptoms could feature acute respiratory distress syndrome and severe pneumonia. Reverse-transcription polymerase chain reaction (RT-PCR) remains the gold standard for diagnosing COVID-19. Unfortunately, it has high cost, extensive waiting time, and low availability in remote areas. Therefore, we developed the Udayana COVID-19 Scoring System (UCSS) for quick detection of COVID-19. This study aims to determine the cutoff score and measure the sensitivity and specificity of the UCSS. We conducted an observational cross-sectional study from June 2020 to July 2020. A questionnaire consisting of 3 objective and subjective scores assesses COVID-19 symptoms and risk factors. Participants were patients suspected of COVID-19 awaiting RT-PCR test results. The UCSS total score then compared with the RT-PCR test result and analyzed to determine the cutoff score, sensitivity, and specificity. 150 participants were included in this study (74 male, 49.3%; mean age 42 ± 15.7). The UCSS total score was significantly correlated with RT-PCR test result (p-value = 0.000). The receiving operator characteristic analysis showed an optimal cutoff score of 7, with a sensitivity of 72% and specificity of 71%. Therefore, the UCSS’ accuracy is at a moderate level. The UCSS showed acceptable sensitivity and specificity, and has the potential to be used as a diagnostic aid for COVID-19 early detection. Further study in diverse areas and larger sample size are needed.